'Let us know you're locked': Pirate radio broadcasts as historical and musical artefact. Issue 2 (15th May 2020) - de Lacey, Alex
Abstract : Pirate radio is one of the pillars of grime music. This arena acts as both a communal and artistic space for musicians to coalesce and create on a regular basis. Its recordings, however, are rarely utilized as part of musical and historical enquiry. Prior investigation has principally focused on studio recordings, specifically the album. This article makes the case for listening again to pirate radio broadcasts, demonstrating how these artefacts act as a historical and musical referent. This is achieved through the analysis of recordings from 2001–2005 alongside ethnographic interviews with practitioners, examining the intense locational claustrophobia, communal conviviality, and entrepreneurial spirit possessed by these artists and their listenership. Pirate radio captures music as process and—unlike static recordings—is a medium that allows for long form extemporization and extra-musical assertions, consequently offering an unparalleled insight into the sociohistorical state of play in London at the turn of the millennium.